(untitled) (TAJ: Journal of Teachers Association, 2011)
The study was carried out to identify the compound responsible for hypolipidemic and hypoglycemic effects of Cajanus cajan (redgram). The methanol extract of redgram seeds was found to decrease fasting blood glucose and lipid profile (p<0.001) on streptozotocin-induced mice compared to control. This activity- guided fraction led to the isolation of a compound, substituted benzene containing polyhydroxy functions fused with lactone (CCA3) by analysis of 1H and 13C-NMR data. Biological studies of the isolated compound possessed prominent hypolipidemic activity. Although a number of hypoglycemic compounds are reported, yet not any hypolipidemic compound from redgram. The compound CCA3 seems to be the first report on hypolipidemic activity from methanol extract of redgram. TAJ 2011; 24(1): 6-10